Viral infection and pulmonary hypertension: is there an association?. (April 2011) - Cool, Carlyne D; Voelkel, Norbert F; Bull, Todd
Pulmonary arterial hypertension (PAH) may be idiopathic, familial or associated with various disease processes. The vascular lesions common to all are the plexiform lesions. It is well documented that the plexiform lesions are angioproliferative, but what leads to this angioproliferation is not so clear. Here, we consider the association of viruses, including HIV, human herpesvirus-8, hepatitis B and hepatitis C, with angioproliferation and the development of PAH. The pathogenesis of viral infections often involves proangiogenic and prosurvival signals, similar to the signals found in the phenotypically abnormal endothelial cells of PAH. However, viral infections alone are unlikely to lead to PAH because –– much like the viral induction of cancers –– additional cofactors, including genetic predisposition, are undoubtedly required for the development of disease. In this article, we also discuss how a dysregulated immune system, in conjunction with a viral infection, could cause PAH. Both autoimmune diseases and viruses are associated with defects in the immune regulatory system, primarily in the T-cell system. These T-cell defects may be a common pathway for the formation of plexiform lesions. Regardless of the route by which viruses may lead to PAH, it is important to recognize their role in this rare disease. Studies of viral pathways in angioproliferation –– both in vitro and in animal models –– may lead to novel therapeutic targets in PAH.